Activation of Nrf-2 Transcription Factor and Caspase Pathway with Royal Jelly Reduces Fluoride Induced Testicular Damage and Infertility in Rats - Parlak, Gozde; Aslan, Abdullah; Turk, Gaffari; Kuloglu, Tuncay; Balgetir, Merve Kavak; Gok, Ozlem; Cinkara, Serap Dayan (Springer Heidelberg, 2023)
This study was carried out to investigate the protective properties of royal jelly on the testicular tissue of rats with testicular damage by giving fluoride. Sperm motility, epididymal sperm density and abnormal sperm ratios were examined and visualized with a light microscope. Expression levels of Caspase-3, Bcl-2, Nrf-2, NF-?B, COX-2, TNF-a and IL1-a proteins in testis tissue were determined by western blot technique. As a result of the study, MDA level, expression level of Bcl-2, NF?B, COX-2, TNF-a and IL1-a proteins, abnormal sperm rates were found higher in Fluoride-50 and Fluoride100 groups compared to other groups. In addition GSH, Catalase enzyme levels, expression levels of Caspase-3 and Nrf-2 proteins were found to be higher in Fluoride + Royal Jelly groups compared to Fluoride-50 and Fluoride-100 groups. In addition, lower degeneration of testicular tissue was found in the histological evaluation in the Fluoride + Royal Jelly groups compared to the other groups. When the data are evaluated royal jelly provides effective protection against testicular damage. From this point of view, we hope that similar results will be obtained when royal jelly is tested on humans.
Keywords: Fluoride; Proteins; Royal jelly; Sperm parameters; Testicular damage